Employee Surveillance Using Algorithmic Management Based on Artificial Intelligence Systems - Breskienė, Ineta (Teisė, 2024)
The article analyses the legal regulation of employee surveillance managed by employers carried on algorithmic management based on artificial intelligence systems. Employers observe employees and their work so that to smoothly organize work processes at workplaces, ensure efficient use of resources, and manage risks. Through the process of surveillance, personal data of employees are collected, which are later analysed; hence, employees may experience direct legal consequences (for example, termination of employment, violations of work duties, adjusted wages, etc.). Algorithmic management based on artificial intelligence systems generates various risks to employees. Before starting their application, employers have to evaluate various requirements. The key requirements arise from the Artificial Intelligence Act, the General Data Protection Regulation and the practice formed by the European Court of Human Rights which has been established regarding employee surveillance. Also, the employer has the obligation to ensure the employee’s privacy rights, since, when applying algorithmic management, artificial intelligence systems can sometimes make hardly predictable insights and reveal extremely sensitive facts about the employee. The issue of informing and consulting employees and their representatives regarding the implementation and use of algorithmic management based on artificial intelligence systems in the work environment is analysed.
Keywords: algorithmic management; artificial intelligence systems; surveillance; personal data; privacy; employees; employees’ representatives